Back to Sports After Arthroscopic Revision Bankart Repair. Issue 2 (16th February 2018) - Buckup, Johannes; Welsch, Frederic; Gramlich, Yves; Hoffmann, Reinhard; Roessler, Philip P.; Schüttler, Karl F.; Stein, Thomas
Background: Recurrent instability following primary arthroscopic stabilization of the shoulder is a common complication. Young, athletic patients are at the greatest risk of recurring instability. To date, the literature contains insufficient description regarding whether return to sports is possible after revision arthroscopic Bankart repair. Hypothesis: Patients presenting with recurrent instability after primary arthroscopic stabilization should expect limitations in terms of their ability to partake in sporting activities after revision surgery. Study Design: Case series; Level of evidence, 4. Methods: Twenty athletes who underwent arthroscopic revision stabilization of the shoulder after failed primary arthroscopic Bankart repair were included in the study after completing inclusion and exclusion criteria surveys. Athletic Shoulder Outcome Scoring System (ASOSS), Shoulder Sport Activity Score (SSAS), and the Subjective Patient Outcome for Return to Sports (SPORTS) scores were determined to assess the participants' ability to partake in sporting activities. Furthermore, sport type and sport level were classified and recorded. To assess function and stability, Rowe, American Shoulder and Elbow Surgeons, Constant-Murley, and Walch-Duplay scores were measured and recorded. Results: Follow-up consultations were carried out after a mean of 28.7 months. The mean age at follow-up examination was 27.75 years. At the time of follow-up, 70% of the patients were able to return to their original sporting activities at the same level. However, 90% of patients described a limitation in their shoulder when participating in their sports. At 28.7 months after surgery, the mean ASOSS score was 76.8; the SSAS score decreased from 7.85 before first-time dislocation to 5.35 at follow-up ( P < .005). The SPORTS score was 5.2 out of 10 at the follow-up consultation. Function- and instability-specific scores showed good to excellent results. The mean external rotational deficit for high external rotation was 9.25°, and for low external rotation it was 12°. Conclusion: Patients can return to their original type and level of sport after arthroscopic revision Bankart repair, but they must expect persistent deficits and limitations to the shoulder when put under the strains of sporting activity. Patients with shoulder injuries who partake in sports that put greater demand on the shoulder show the smallest probabilities of returning to sporting activity.